Swim bladder mycosis in pretty tetra (Hemigrammus pulcher) caused by Exophiala pisciphila and Phaeophleospora hymenocallidicola, and experimental verification of pathogenicity - Řehulka, J; Kubátová, A; Hubka, V (Journal of fish diseases, 2018)
Spontaneous invasive and chronic disseminated mycosis affected Hemigrammus pulcher kept in a public aquarium, and infection was manifested by inappetence, exophthalmia, erratic swimming, eroded scales, anaemia of the gills and abdominal distension. Internally, there was a grossly swollen swim bladder with a thickened wall filled with a dark mass. The body cavities contained a clear, light amber fluid and a swollen intestine which was full of a watery fluid containing small gas bubbles. Histopathology revealed a granulomatous inflammatory response with fungal hyphae in the lumen and wall of the swim bladder, hepatopancreas, spleen and kidneys with signs of nephrohydrosis. Exophiala pisciphila and Phaeophleospora hymenocallidicola were isolated from the swim bladder, abdominal cavity and gastrointestinal tract. The exogenous source of infection was probably the ample wooden decoration and plants inside the aquarium. Koch's postulates were fulfilled by re-isolation of both fungal species from fish artificially infected under laboratory conditions. As P. hymenocallidicola is less capable of defence against phagocytosis, E. pisciphila probably played a major role. Severe clinical manifestations with 100% mortality developed in two fish species infected by E. pisciphila. A significant increase in the plasma levels of amino acids was observed as a result of the activation of proteolysis.
Keywords: Ascomycota; vzdušné vaky; mykózy; Air Sacs; nemoci ryb; experimental infection; blood plasma amino acids; Animals; Mycoses; Exophiala; Characidae; zvířata; mycotic granuloma; Fish Diseases; black yeasts